Feasibility of a Transcutaneous Tibial Nerve Stimulation Device Use in Overactive Bladder Patients: A Pilot Study From a Single Tertiary Care Center - Li, Xunhua; Li, Xing; Zhou, Zhonghan; Zhao, Hui; Liao, Limin (Frontiers in Neurology, 2022)
ABSTRACT Purpose: To evaluate the preliminary efficacy, safety, and acceptability of a transcutaneous tibial nerve stimulation (TTNS) device in overactive bladder (OAB) patients. Methods: Twenty OAB patients who failed with conservative treatments were recruited consecutively. All patients received 60 minutes of daily unilateral stimulation for 4 weeks using a smart wearable transcutaneous tibial nerve stimulation device and the stimulations were at 20 Hz frequency, 200 µs pulse width. OAB symptoms were observed at baseline and week 4, using a 3-days voiding diary, the overactive bladder symptom score (OABSS), the perception of bladder condition (PPBC), and the American Urological Association Symptom Index Quality of Life Score (AUA-SI-QoL). Urodynamic characteristics were measured to determine the pilot efficacy of the device during the treatment comparing the baseline parameters to the post-treatment parameters. Results: Among the patients,15 cases were OAB-dry and 5 cases were OAB-wet. All patients were evaluated at the end of the study and no significant side effects were found during the treatment. The daily micturition frequency and the number of incontinence episodes per day were reduced from 15.10±1.61 to 12.00±4.56, and 3.20±0.80 to 0.47±0.38, respectively. The mean voiding volume was increased from 130.10±53.07 mL to 157.30±66.95 mL. The OABSS, AUA-SI-QoL, and PPBC were reduced from 9.35±1.39 to 5.9±2.36, 5.70±0.47 to 3.85±1.04, and 5.70±0.47 to 4.35±0.86, respectively. The first sensation of bladder filling (1st SBF), maximal bladder capacity (MBC), and mean compliance were increased from 87.50 (60.00-167.50) mL to 150.00 (104.00-211.30) mL, 175.00 (120.30-354.00) mL to 255.00 (151.50-491.50) mL and 36.67 (12.44-39.69) mL/cmH2O to 40.00 (20.00-52.50) mL/cmH2O, respectively. The maximum detrusor pressure (Pdet. max) was reduced from 14.50 (5.00-35.25) cmH2O to 11.00 (6.00-20.00) cmH2O. Conclusions: The preliminary results demonstrated that the TTNS device was safe, effective, and acceptable to use in OAB patients, but the results need to be substantiated by conducting more randomized controlled studies further.